METODE CEPAT MENGHAFAL HADIS SANAD DAN MATAN BAGI REMAJA MASJID - Juriono , Juriono (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
The "Quick Method for Memorizing Hadith Sanad and Matan" was initially a small book written by a hadith expert named Dr. Ahmad Lutfi Fathullah. Through this small book, the author attempted to test the method in the form of community service by applying it. The target group for this experiment was the youth of Masjid Al-Ma'ruf, conducted over the course of one month, resulting in significant outcomes. The conclusion drawn was that within a relatively short period, the youth were able to memorize more than 40 hadiths, complete with their sanad and matan.